Perfil clinicoepidemiológico dos melanomas cutâneos em duas instituições de referência na cidade de Manaus, Brasil Clinical and epidemiological profile of cutaneous malignant melanomas in two referral institutions in the city of Manaus, Brazil - Fabiano Bandeira Chiba; Antonio Pedro Mendes Schettini; Ana Carolina Guimaraes Delfino; Carlos Alberto Chirano; Silvana de Albuquerque Silva Damasceno (Anais Brasileiros de Dermatologia, 2011)
O conhecimento da frequência e das características clinicoepidemiológicas do melanoma cutâneo nas diversas regiões do Brasil é importante para avaliar a magnitude do problema e direcionar adequadamente as ações de saúde. Neste estudo, revisaram-se os dados de 55 pacientes com melanoma cutâneo atendidos em duas instituições de saúde da cidade de Manaus. Verificou-se maior frequência entre homens pardos, na oitava década de vida, com lesões do tipo melanoma acrolentiginoso nos membros inferiores, com Breslow maior que 1mm e Clark nível V. Knowledge on the frequency and clinical and pathological characteristics of cutaneous melanoma in the different geographical regions of Brazil is important in evaluating the magnitude of the problem and in directing healthcare actions appropriately. The present study reviewed data from 55 cases of cutaneous melanoma in patients treated at two healthcare institutions in the city of Manaus, Amazonas, Brazil. Rates were higher in brown-skinned males and in individuals of 70-80 years of age. Lesions were most commonly located on the lower limbs, were of the acral lentiginous melanoma type and at advanced stages of the disease, with Breslow thickness > 1 mm and Clark level V.